Finding the mitral annular lines from 2-D + 1-D precordial echocardiogram using graph-search technique. - Yu-Tai Ching (IEEE Transactions on information technology in biomedicine)
The apical four-chamber view echocardiogram collected by a transthoracic transducer can be used to evaluate the left ventricle volume. In the diastole, the left ventricle and left atrium become one chamber. In this case, the left ventricle and left atrium need to be separated using a "mitral annular line" so the volume of the left ventricle can be estimated. In this paper, a nearly automatic method for identifying the mitral annular lines from two-dimensional (2-D) + one-dimensional (1-D) precordial four-chamber view echocardiogram is presented. This method employs the optical flow technique and graph-search approach. The mitral annular line sequence is found by finding the shortest path in a weighted directed graph. The vertices in the graph are candidates for the mitral annular lines. The weights on the directed edges are determined using the optical flow technique. The proposed method requires only a physician to provide a point that is always in the left ventricular chamber. Experimental results show that the average error for the left ventricle volume obtained based on the computed mitral annular lines is 3%.